Identification of Academic Stress of the 1st Year and the 2nd Year English Education Students at University in Pekanbaru - Risa Maharani; Rizky Gushendra (Journal of English and Arabic Language Teaching, 2024)
The purpose of this research were to describe the level of academic stress in the 1st year and the 2nd year of English Education students and to examine whether there is a significance difference of the academic stress between the 1st year and 2nd year of English Education Students. This research was a survey design on quantitative approach. The population of the research was the 1st year and the 2nd year of English Education students at UIN Suska Riau. By having simple random sampling, it has been selected 97 first-year students from a total population 125 students and 108 second-year students from a total population 146 students. To collect the data, the researcher used a questionnaire to know the level of academic stress in the 1st year and 2nd year of English Education students. The data were analyzed by Descriptive Statistic and Inferential Statistic (non-parametric) because the data were not normally distributed using Mann-Whitney U Test on the SPSS version 21.0 program. The result of the data analyze showed that the level of academic stress in the 1st year of English Education students was at a low category, with 50 students (51.5%) and the level of Academic Stress in the 2nd year of English Education Students was also at a low category, with 48 students (44.4%). It can be concluded that there was no a significance difference of the Academic Stress level between the 1st year and the 2nd year of English Education Students at UIN Suska Riau.